Spam Comment Detection on YouTube Using Random Forest ML Technique - C. Lakshman,; S. Noortaj, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This project has focused on the spam comment detection problem in YouTube comments. YouTube is gaining fame day by day as a platform for users to communicate with one another through comments. The core purpose of spam detection is to maintain the quality of the platform itself. In this study, four machine learning models-RF, SVM, LSTM, and ExtraTree-are assessed for their ability to identify spam comments. The properties of the RF might also have been equipped with great findings at the remarkable rate of 95% and were thus seen as worthy for being able to handle with very large datasets and complex patterns in general. The ExtraTrees Classifier, on the other hand, performed similarly to the SVM model, having also attained the same impressive high degree of accuracy-95%. The LSTM, on the contrary, poorly performed with an accuracy of 95%, exposing its demerit.
Keywords: YouTube; Machine Learning; Spam Detection; RF; SVM; LSTM; ExtraTrees Classifier; Classification; Accuracy; Algorithm Comparison; Comment Filtering; Spam Comments